Forms of constraint: a history of prison architecture - Johnston, Norman Bruce (University of Illinois Press, 2000)
Makeshift prisons -- Religious and monastic imprisonment -- Stirrings of reform : prisons in the early modern period -- A passion to peek : 1780 to 1835 -- Great expectations : prison reform in North America until mid-nineteenth century -- Western European prisons : 1840 to World War II -- Eastern Europe, Asia, and the Americas : 1840 to World War II -- Old problems, new solutions